Faktor Internal dan Eksternal yang Memengaruhi Kualitas Audit - Mahadewi, I Gusti Agung Candrika; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi; Vol 32 No 6 (2022)DO - 10.24843/EJA.2022.v32.i06.p15, 2022)
The resulting financial reports are important to determine the performance of companies and government agencies, so it is necessary to carry out an audit. This study aims to obtain empirical evidence of the effect of professional skepticism, work experience, independence, and work environment on audit quality. Data was obtained by distributing questionnaires to the Bali BPK Office. The sample in this study was 54 auditors, determined by using purposive sampling technique. The analytical tool used is multiple linear regression. The results of the study of the four independent variables, namely professional skepticism, work experience, independence, and work environment have a significant positive effect on audit quality, so that the higher the level of professional skepticism, work experience, independence, and the more conducive the auditor's work environment will be, it will greatly affect the quality of audit results. which is getting better. Keywords: Professional Skepticism, Work Experience, Independence, Work Environment, Audit Quality.